Clonal propagation of Carob (Ceratonia siliqua L., Fabaceae) - Hakim, L; Islam, MR; Mamun, ANK; Ahmed, G; Khan, R (Bangladesh Journal of Botany, 2010)
Mature seeds of carob tree (Ceratonia siliqua L.) were germinated on hormone free MS medium. Efforts were made to develop multiple shoots by using axillary buds of in vitro grown seedlings on MS medium fortified with different concentrations of BA singly and BA in combination with IAA or GA3. Axillary buds produced single shoot with a moderate amount of callus at the base of the explant after culturing on MS medium with BA alone. Multiple shoots were regenerated when explants when cultured on MS medium fortified with BA + IAA or BA + GA3. MS medium supplemented with 1.5 mg/l BA + 0.5 mg/l GA3 was found more effective in multiple shoot regeneration than all other combinations. Regenerated multiple shoots were excised and cultured on half strength of MS medium containing different concentrations of IBA for root induction. Best root development was obtained in half strength MS medium containing 0.5 mg/l IBA. About 70% of the regenerated plantlets survived in natural conditions. Key words: Carob; Ceratonia siliqua; Fabaceae; Clonal propagation DOI: 10.3329/bjb.v39i1.5520 Bangladesh J. Bot. 39(1): 15-19, 2010 (June)